Mapping Urban Green Space Fragmentation using Drone Technology in Banjarbaru City - Rizali, Akhmad; Abbas, Saipul; Marsuni, Yusriadi; Sari, Yulia Padma; Farah, Nurin Nisa; Noorkomalasari, Noorkomalasari; Badaruddin, Badaruddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The rapid urban growth in Banjarbaru City has significantly impacted the quality and quantity of green open spaces. Fragmentation of green spaces poses a major challenge in maintaining the city's ecological balance, particularly amidst high urbanization rates. This study aims to analyze the distribution and fragmentation level of green spaces across five sub-districts in Banjarbaru City using drone technology and spatial approaches. Data were collected through high-resolution aerial mapping and spatially analyzed to identify fragmentation patterns and compare them with the 2024-2043 Spatial Planning (RTRW) of Banjarbaru City. The results show that the highest fragmentation occurs in the Landasan Ulin and South Banjarbaru sub-districts, characterized by small patches and low core vegetation areas. Meanwhile, North Banjarbaru, Cempaka, and Liang Anggang sub-districts still retain extensive and connected green spaces. A comparison with the RTRW reveals a deviation between the planned and actual conditions, particularly in areas designated to be preserved as green open spaces.